Prediction of body water compartments by raw bioelectrical impedance parameters in athletes: Comparison between series and parallel measurements - Francisco, R.; Jesus, F.; Nunes, C. L.; Carvalho, A.; Alvim, M.; Campa, F.; Sardinha, L. B.; Mendonca, G. V.; Lukaski, H.; Silva, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background The aim of this study was to determine the predictive role of series and parallel bioelectrical impedance-derived parameters in predicting total body (TBW), intracellular (ICW), and extracellular water (ECW) in athletes.